Albert Camus’ absurdity and rebellion in Kurt Vonnegut’s “The Sirens of Titan” (2024)
Abstract: This literary analysis explores Kurt Vonnegut’s characters in the novel The Sirens of Titan through Albert Camus’ philosophy of absurdism. I analyze the four main characters’ journeys from absurd awareness to the facing of absurdism as well as focusing on the actions of the character Winston Niles Rumfoord. This analysis takes into account Camus’ absurdism and rebellion in The Myth of Sisyphus and The Rebel. The analysis shows the different ways and discrepancies in the evolution of the characters when accepting the absurd quality of life.